Analysis of mapping knowledge domains of special education research: a comparison of CSSCI and SSCI indexes. - Lu, Cuiwei; Li, Deyang; Ren, Jie; Liu, Huanmin; Zhang, Xueqin (International Journal of Developmental Disabilities, 2022)
Special education is a natural yardstick to measure a country's educational level and the whole civilization. China has a massive special education undertaking that develops rapidly and forms a unique system. This study used bibliometric methods to conduct a macroscopic comparative analysis of Chinese and global literature, discuss the existing problems of China's special education, and put forward relevant recommendations accordingly. The CiteSpace V visual analysis software was used to draw the scientific knowledge map of the Chinese local database CSSCI and the global database SSCI, and the results of the map were discussed. Research conclusions: Firstly, China's research institutions lack a macro-level cooperation network. Second, there are differences in the focus of special education objects between China and the world. This difference is mainly caused by the definition of special education objects, which may be influenced by the formulation of educational concepts and policies. Thirdly, in the reference co-citation analysis, the focus of Chinese research is narrow and generally focuses on special education teachers. This article provides implications for solving special education problems in China, and its research method provides a reference for future related research for other countries.